(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Depression is a health problem in the world that has affected more than 300 million people around the globe. This health problem is characterized by feeling sad, depressed, irritability as well as distortion of cognition such as self-criticism, feeling of guilt, feeling of worthlessness, lower self-confidence, pessimism and hopelessness where their manifestations may vary for each individual. Method: In this study, it compares the fluoxetine group combination of Rational Emotive Behavior Therapy (REBT) with the fluoxetine group in the treatment of reducing symptoms of depression and improving cognitive function. This research is an experimental research with pre-test and post-test control group design. The sampling technique was done by using consecutive sampling for each group. Results: From the results of the study it was found that the mean of Hamilton Depression Rating Scale (HDRS), the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina) and Brain-Derived Neurotrophic Factor (BDNF) serum levels in the samples given by both groups experienced statistically improvements. Conclusion: there is an effect on the provision of fluoxetine therapy combination of REBT compared to fluoxetine therapy alone in improving depressive symptoms, cognitive function as well as increasing BDNF serum levels.